Implementação de topologia de redes utilizando MPLS - Caetano, Junior Cesar (2013)
This monograph aims to present the main features existents in MPLS (Multiprotocol Label Switching), focusing on the implementation of Quality of Service (QoS). In the first part of this paper presents some basic concepts of MPLS technology, along with a brief description of its operation. Also described are the main services available, such as the creation of a VPN (Virtual Private Network) management using Traffic Engineering and implementation of QoS in MPLS. Finally, some examples are presented to implement QoS over MPLS.